2009
DOI: 10.1002/adfm.200801319
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Red Phosphorescent OLEDs based on Non‐Conjugated Silicon‐Cored Spirobifluorene Derivative Doped with Ir‐Complexes

Abstract: A novel host material containing silicon‐cored spirobifluorene derivative (SBP‐TS‐PSB), is designed, synthesized, and characterized for red phosphorescent organic light‐emitting diodes (OLEDs). The SBP‐TS‐PSB has excellent thermal and morphological stabilities and exhibits high electroluminescence (EL) efficiency as a host for the red phosphorescent OLEDs. The electrophosphorescence properties of the devices using SBP‐TS‐PSB as the host and red phosphorescent iridium (III) complexes as the emitter are investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(65 citation statements)
references
References 39 publications
1
64
0
Order By: Relevance
“…This device architecture resembles those reported in the literature, [20] with PEDOT:PSS and a-NPD functioning as holeinjection and hole-transport layers, respectively. To further improve the efficiency and decrease the hole-injection barri- er, we inserted a thin layer of TCTA between the NPB layer and the EML to function as both a hole-transporting material and an exciton blocker (E T = 2.76 eV) [21] preventing diffusion of excitons to the a-NPD layer. TPBI functioned as both a hole-blocking and electrontransporting layer; [22] LiF was the electron-injection material.…”
Section: Abstract In Chinesementioning
confidence: 99%
“…This device architecture resembles those reported in the literature, [20] with PEDOT:PSS and a-NPD functioning as holeinjection and hole-transport layers, respectively. To further improve the efficiency and decrease the hole-injection barri- er, we inserted a thin layer of TCTA between the NPB layer and the EML to function as both a hole-transporting material and an exciton blocker (E T = 2.76 eV) [21] preventing diffusion of excitons to the a-NPD layer. TPBI functioned as both a hole-blocking and electrontransporting layer; [22] LiF was the electron-injection material.…”
Section: Abstract In Chinesementioning
confidence: 99%
“…Gao et al reported a pyridine/carbazole hybrid, 4,7-dicarbazol-9-yl-[1,10]-phenanthroline (BUPH1), [8] for Ir(ppy) 3 -based green device, while Lee et al used a non conjugated silicon-cored spirobifluorene derivative (SBP-TS-PSB) as a host material for the red phosphorescent Ir(III) complexes. [9] Recently, Ma et al reported a carbazole/oxadiazole hybrid molecule o-CzOXD [2] for both green and red phosphorescent devices. It still is a great challenge to design and synthesize a bipolar material with a high enough triplet energy gap that is suitable for use as a blue phosphorescent dopant and with a balance of hole and electron fluxes that can lead to excellent performance of the device.…”
mentioning
confidence: 99%
“…In these two devices, we choose TCTA as the exciton blocker to prevent exciton diffusion to the hole transporting layer. TCTA has been proven to be an efficient exciton blocker for red phosphorescence devices, [9] It is noteworthy that for devices B1 and B2, we used mCP instead of TCTA as the exciton blocker, because the triplet energy (E T ¼ 2. , respectively. The CIE values for this red device are (0.67, 0.33) at 6 V. All these BCPO-based blue, green and red devices revealed very low turn-on voltage ( 3 V) and extremely high external quantum, current and power efficiencies.…”
mentioning
confidence: 99%
“…When two spirobifluorene units with the feature of ambipolarity are attached to non-conjugated tetraphenylsilane inert core, a bipolar and thermally stable molecule, bis(4′-(9,9-di-phenyl-9H-fluoren-2-yl)biphenyl-3-yl)diphenylsilane (SBP-TS-PSB (46), T g = 194 °C, Figure 13), with high triplet energy of 3.04 eV is achieved [90]. (piq) 2 Ir(acac) (6) and SBP-TS-PSB (46) based red PhOLED shows a maximum efficiency of 14.6% (10.3 lm/W).…”
Section: Bipolar Hostsmentioning
confidence: 98%